2017
DOI: 10.1016/j.actbio.2016.11.016
|View full text |Cite
|
Sign up to set email alerts
|

3D culture of human pluripotent stem cells in RGD-alginate hydrogel improves retinal tissue development

Abstract: The burden of retinal disease is ever growing with the increasing age of the world-wide population. Transplantation of retinal tissue derived from human pluripotent stem cells (PSCs) is considered a promising treatment. However, derivation of retinal tissue from PSCs using defined media is a lengthy process and often variable between different cell lines. This study indicated that alginate hydrogels enhanced retinal tissue development from PSCs, whereas hyaluronic acid-based hydrogels did not. This is the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(89 citation statements)
references
References 103 publications
1
75
0
2
Order By: Relevance
“…Этот результат показал, что альгинатные инъ-екционные и самовосстанавливающиеся гидрогели обладают большим потенциалом для восстановле-ния центральной нервной системы. Недавно группа Lako разработала альгинатные гидрогели, конъюги-рованные с клеточным адгезивным пептидом RGD (Arg-Gly-Asp) для усиления клеточной активнос-ти гидрогелей [14]. Пептидные звенья ковалент-но встраивали в альгинатный полимерный каркас с последующей сшивкой полимерного хлоридом кальция (CaCl 2 ).…”
Section: +unclassified
See 1 more Smart Citation
“…Этот результат показал, что альгинатные инъ-екционные и самовосстанавливающиеся гидрогели обладают большим потенциалом для восстановле-ния центральной нервной системы. Недавно группа Lako разработала альгинатные гидрогели, конъюги-рованные с клеточным адгезивным пептидом RGD (Arg-Gly-Asp) для усиления клеточной активнос-ти гидрогелей [14]. Пептидные звенья ковалент-но встраивали в альгинатный полимерный каркас с последующей сшивкой полимерного хлоридом кальция (CaCl 2 ).…”
Section: +unclassified
“…This result suggested that alginate-based injectable and self-healing hydrogels have great potential in central nervous system repair applications. Recently, the Lako group developed alginate hydrogels conjugated with cell adhesive peptide (Arg-Gly-Asp, RGD) to enhance cellular activity of the hydrogels [14]. They covalently conjugated the peptide sequences into the alginate polymer backbone and fabricated hydrogels using calcium chloride (CaCl 2 ).…”
Section: Physical Crosslinking Reactionsmentioning
confidence: 99%
“…However, despite these impressive advances, many gaps remain in our understanding of the molecular mechanisms of PR loss, and retinal degenerations remain essentially untreatable. Improvements in the directed differentiation of pluripotent stem cell (PSC) derived retinal cells have shown that PSCs can differentiate into retinal pigment epithelium (RPE) and retinal neurons, including PR cells 215 , and can give rise to 3D ‘mini-retinas’, organized into self-forming multi-layered retinal tissues 6, 1421 . During embryogenesis, the eyefield first appears as an optic vesicle (OV) that evaginates outward from the diencephalon.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, preferential advantages were reported for RGD-alginate scaffold compared to current HA-based hydrogel for retinal cell delivery (Hunt et al, 2017). Indeed, retinal pigmented epithelium (RPE) formation from stem cells has been developed in the presence of RGD alginate scaffold.…”
Section: Cornea Repairmentioning
confidence: 99%